IMPROVING STUDENTS’ SPEAKING SKILL THROUGH THE COMBINATION OF PRESENTATION, PRACTICE, AND PRODUCTION (PPP) METHOD AND TALKING STICK METHOD - Anna Stasya Prima Sari; Ribka Kariani Br. Sembiring (JURNAL LINER (Language Intelligence and Educational Research), 2019)
This research was primarily carried out to prove that the combination of Presentation, Practice, and Production (henceforth, PPP) method and Talking Stick method could improve students’ English speaking skill and to describe the students’ responses towards the combination of PPP method and Talking Stick method in the learning teaching processes of English speaking skill. This research is Classroom Action Research (henceforth, CAR) which was carried out in two cycles. Each cycle consisted of four meetings. The research subject of this CAR are the fifth grade students of State Primary School 028226 Binjai Class V-1 in the Academic Year of 2019/2020.There are 33 students as the research subject. The analysis of quantitative data showed that the students’ mean score increased continually from 55,36 in the pretest, 66,72 in the posttest of cycle 1, to 77,27 in the posttest of cycle 2. The analysis of qualitative data showed that the learning teaching processes of English speaking skill through the combination of PPP method and Talking Stick method ran very well. The students were more active, and motivated to learn English speaking skill. The learning atmosphere was more alive and enjoyable after PPP method and Talking Stick method were implemented in the English speaking classes. It is advisable that English teachers of primary school students combine PPP method and Talking Stick method in order to improve their students’ English speaking skill